Let It Ride! An Empirical Investigation of Problem Gambling and the Implications of Legalized Online Sports Betting - Ozer, Gorkem Turgut; Greenwood, Brad N.; Gopal, Anandasivam (Information Systems Research, 2026)
In 2018, the Supreme Court of the United States struck down the Professional and Amateur Sports Protection Act (PASPA), ending a nearly 30-year federal ban on sports betting and paving the way for dozens of states to legalize such operations. The sports betting market has experienced triple- and double-digit growth every year since the PASPA decision. Yet the downstream consequences of the legalization of sports betting remain understudied. In this paper, we examine the impact of the legalization of both off-line and online sports betting on the well-being of individuals in those jurisdictions. We focus on two outcomes: the number of calls to the National Problem Gambling Hotline and the number of suicides reported per state as a result of legalization of sports betting. Our results indicate that, whereas the number of calls associated with problem gambling is uncorrelated with the legalization of physical sportsbooks, it is strongly correlated with the legalization of online sports betting. Further, results suggest that the legalization of online betting is correlated with an increase in suicides, an outcome historically associated with problem gambling. Finally, we observe that these deleterious effects are more pronounced for certain groups, in particular, for young, unmarried, and less educated men.